Between a rock and a hard place: psychological resilience and intimate relationships among seropositive young adults in Senga, Gweru - Mafunga, Chlodine (Midlands State University, 2018)
The HIV and AIDS virus has continued to portend the livelihood of many young adults undermining their right to psychological wellbeing. Therefore the study was aimed at exploring the views and experience of infected youth aged between 18 to 24 years in Senga, Gweru. Thus revealing the problems which the young adults met in forming and maintaining intimate relationships in the context of the HIV adversity and how it impacted on psychological resilience. This qualitative research was grounded on the social ecological model as the theoretical framework. The Interpretative Phenomenological Analysis was employed as a research design thus data obtained from the 8 in-depth interviews was analysed using thematic analysis. The results indicated that the young adults had suspended their relationships due to seropositity. These young adults had negative self-esteem, feeling of regret and self-blame, support from peers and the society was inaccessible for several participants. The limitations encountered included the under representation of males in the study, limited age appropriate literature and the participation by married women who were young adults that had not been anticipated for. The research recommends programs to improve psychological attributes such as cognitive competence, confidence, self-efficacy, optimism and problem solving skill available to the seropositive youth even after they had been enrolled for ART. Social forums on where young adults can form social ties are also important since youth can engage with people who have the same condition with them.